Digital Innovation and Migrants’ Integration: Notes on EU Institutional and Legal Perspectives and Criticalities - Paola Regina; Emilio De Capitani (Social Sciences, 2022)
These notes describe the evolution of the EU strategy for the integration of Third Country Nationals since the Tampere Program in 1999 until the second Action Program (2021–2027). It highlights the EU’s endeavor to close the gap between migrants and EU citizens in compliance with the EU general anti-discrimination policy and, since the entry of the Lisbon Treaty into force, of the EU Charter of Fundamental Rights. Accordingly, the current integration strategy has a much wider legal and financial basis than the one described by art. 79.2 of the TFEU. This new individual-centered and wide-ranging public approach can now be strengthened through the new European Digital Agenda, whose aim is also to reframe and make the relations between the individual and public administration more user friendly. However, in the human mobility domain, the large EU acquis, which is currently focused on internal security, should be re-balanced from a legislative and operational point of view to avoid the risk of infringing on data protection principles and establishing a mass surveillance framework, which could be incompatible with the EU as a democratic society and a rule of law-abiding organization. Within this very complex framework, a promising development is the establishment of a new European Asylum Agency, which may pave the way for more consistent EU asylum and migration policies.